Recent research on age, second language acquisition, and early foreign language learning - Nikolov, Marianne (Array, 2006)
The aim of this paper is to provide a critical overview of the issues and research conducted since the most recent state-of-the-art article published in the Annual Review of Applied Linguistics by David Singleton (2001). First, a summary of what research has said about the Critical Period Hypothesis (CPH) in cognitive science and neurobiology is given, followed by a review of recent findings of age-related studies since 2000 focusing on what late beginners and adults can achieve, how early and later beginners compare in bilingual programs. The second part of the paper explores language policy and classroom implications of the CPH for foreign language teaching. As English has become the lingua franca, early programs have mushroomed all over the world. However, besides overwhelming enthusiasm, recently critical voices can also be heard. On the one hand, early exposure is often seen as a must, or a key to success and a solution to all problems in language education. On the other hand, it may be perceived as a threat to first language development and identity. Finally, we explore areas for further research.